The current state of digital marketing in our country and ways to develop it - Karimov, Khursid; Karimova, Maftuna (MMIT Proceedings, 2024)
This article analyzes the concept of digital marketing, its types, its introduction into the economy, its status and directions of development in our country. The experience of developed countries in the field of digital marketing has been studied, and conclusions and suggestions have been made regarding the development of digital marketing in our country.